2012
DOI: 10.1002/jgm.2644
|View full text |Cite
|
Sign up to set email alerts
|

Effective, safe nonviral gene transfer to preserve the chondrogenic differentiation potential of human mesenchymal stem cells

Abstract: The data indicate that safe, efficient transgene expression can be achieved in hMSCs over time using the nonviral GeneJammer® compound, showing promise for future therapeutic settings aiming to treat human articular cartilage disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 89 publications
1
24
0
Order By: Relevance
“…The increased therapeutic efficacy, in our study, may be due to the high level of gene expression in cartilage cells achieved by liposome-mediated delivery of recombinant plasmid DNAs (10). Our study verified that the target genes were delivered to the joints, transferred to the synovial cells, which expressed the active product, and the gene product diffused from the synovium to the articular cartilage, functionally influencing the metabolism of cartilage cells (46). Importantly, our in-vivo experiments confirmed that the efficiency of double transfection in promoting functional recovery was better than either of the single transfections.…”
Section: Discussionsupporting
confidence: 86%
“…The increased therapeutic efficacy, in our study, may be due to the high level of gene expression in cartilage cells achieved by liposome-mediated delivery of recombinant plasmid DNAs (10). Our study verified that the target genes were delivered to the joints, transferred to the synovial cells, which expressed the active product, and the gene product diffused from the synovium to the articular cartilage, functionally influencing the metabolism of cartilage cells (46). Importantly, our in-vivo experiments confirmed that the efficiency of double transfection in promoting functional recovery was better than either of the single transfections.…”
Section: Discussionsupporting
confidence: 86%
“…However, again, due to limitation in resources, this present study is dedicated to evaluate immunohistochemistry for collagen type I and II only. Furthermore, many previous papers are showing on immunohistochemistry for collagen type II only (Cao et al, 2011;Elsler et al, 2012;Feng et al, 2011;Song et al, 2013;Wu et al, 2014;Yang et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Because the incidence of spontaneous chondrogenic differentiation of MSCs is very low, many pharmacological and genetic approaches have been developed to induce such differentiation (12). SRY-related high-mobility-group box 9 (Sox9) gene is a cartilage-specific transcription factor and plays essential roles in chondrocyte differentiation and cartilage formation (13).…”
Section: Introductionmentioning
confidence: 99%